Corn Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Shoup, Douglas (My University, 2012)
This publication provides estimated cost and returns for forward farm planning for corn in south central Kansas.
MF2157_2012_12
Keywords: MF2157; Crops; Economics; MF